2009
DOI: 10.1002/bdra.20555
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of clinical characteristics of amniotic rupture sequence with and without body wall defect: Further evidence for separation

Abstract: This observation suggests that amniotic band adhesion in ARS-L takes place at a later development stage. Although limited by a small sample size, our study contributes to the growing evidence that both ARS entities represent two nosologically distinct conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
5
1
Order By: Relevance
“…ACASS only classified deficiencies of the phalanges as digital deficiencies, while other authors may have included deficiencies of the metacarpals/metatarsals as digital deficiencies. Most of our cases with BWD did not have digital deficiencies which was also the case for Jamsheer et al [] and Orioli et al [] but had more severe limb deficiencies such as complex types or total limb deficiencies as defined in Bedard et al [] (Table ). This supports the argument by Martinez‐Frias [] that the amniotic bands in cases with BWD should be considered different from those without BWD.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…ACASS only classified deficiencies of the phalanges as digital deficiencies, while other authors may have included deficiencies of the metacarpals/metatarsals as digital deficiencies. Most of our cases with BWD did not have digital deficiencies which was also the case for Jamsheer et al [] and Orioli et al [] but had more severe limb deficiencies such as complex types or total limb deficiencies as defined in Bedard et al [] (Table ). This supports the argument by Martinez‐Frias [] that the amniotic bands in cases with BWD should be considered different from those without BWD.…”
Section: Discussionsupporting
confidence: 76%
“…Digital deficiencies were the most frequent particularly for cases with amniotic bands and limb deficiency (Table ). However, the proportion with digital deficiencies is lower than that reported by Froster and Baird [] and Jamsheer et al []. The variation may be attributed to small numbers and/or to differences in classification.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…For instance, on an epidemiological basis, Martinez-Frias (1997b) concluded that the body wall complex (BWC) consisted in a BWD with or without AB and that AB with a BWD have a different origin than those without such a defect (Martinez-Frias, 1997a). Jamsheer et al (2009) shared this last conclusion. However, Levy, Lacombe, Rougier, and Camus (2007) reported the occurrence of AB in two sibs; one of them also presented a BWD, exencephaly, and limb deficiencies, the other only minor digital amputations and constriction rings, shedding doubts on this conclusion.…”
Section: Funding Informationmentioning
confidence: 97%
“…5,6 Anomalies are limited to external structures with or without body wall disruption or internal malformations that vary in severity and location. [7][8][9] Some authors consider ABS separately from the limb-body wall complex (LBWC), body wall defects (BWD) or the body wall complex (BWC), [10][11][12] whereas others believe these are all part of the same disease. [13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%